Modelos de atención asociados a la satisfacción del paciente ambulatorio en establecimientos de salud - Tejerina Ruggeroni, Adriana (2014)
Patient-physician relationship satisfaction depends on several variables, including models of care (paternalistic, deliberative or consumer). The aim of this study is to determine whether an association exists between satisfaction and the healthcare model used. Secondary objectives are to determine whether patient satisfaction is associated with their gender, their age and the number of consults received. Methods: 415 participants of a public and private health center completed a questionnaire with demographic data, models of care used and level of satisfaction (questionnaire CREM-P). Results: We used the Poisson regression that models consumerism (OR: 1,39, 95% CI :1,04-1,85) and deliberative (OR: 1,35, 95% CI: 1,04-1,75) were associated with greater satisfaction. The medical center, patient´s age and the number of consults received were associated with higher levels of satisfaction. There is no association between the models of care and physician age or socioeconomic status. Conclusion: The most widely used model of care is paternalistic although it’s the one causing lower levels of satisfaction.